Antitumor Effects of Hydromorphone on Human Gastric Cancer Cells in vitro [Retraction] - Liang B; Li C; Zhou Z; Xie Y (Dove Medical Press, 2024)
Liang B, Li C, Zhou Z, Xie Y. Drug Des Devel Ther. 2023;17:1037–1045. We, the Editor and Publisher of the journal Drug Design, Development and Therapy have retracted the published article. Following publication of the article, concerns were raised about the duplication of images from Figure 4. Specifically, Images for Figure 4A, Migration, 0 and 200; 400 and 800; and Invasion, 0 and 400 have been duplicated. The corresponding author did not respond to our queries and was unable to provide a satisfactory explanation for how the images came to be duplicated or provide satisfactory original data for the study. As verifying the validity of published work is core to the integrity of the scholarly record, the Publisher and Editor requested to retract the article and the corresponding author was notified of this decision. We have been informed in our decision-making by our editorial policies and COPE guidelines. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.